Effect of corn shredlage on feed intake, rumen fermentation, and lactation performance of dairy cows fed a low-fibre diet - Miroslav Joch; Václav Kudrna; Alena Výborná; Yvona Tyrolová; Filip Jančík; Petra Kubelková; Mariana Vadroňová; Denisa Tichá (Italian Journal of Animal Science)
Corn shredlage is a whole-plant corn silage with a greater proportion of long particles and intensively processed stalks (by shredding and peeling) and kernels (by thorough crushing). Corn shredlage may improve rumen function and milk performance of dairy cows, especially in low-fibre diets. Paradoxically, little is known about the specific effects of corn shredlage on rumen fermentation. This study aimed to understand how the dietary replacement of corn silage with corn shredlage changes feed intake, rumen fermentation, rumination time, and milk performance of dairy cows fed a low-fibre diet. Thirty-four lactating cows were allocated to two dietary treatments in a crossover design with two 30-day periods. The dietary treatment was a total mixed ration with either 1) 25% conventionally processed corn silage (CON; 14-mm theoretical length of cut, TLOC) or 2) 25% corn shredlage (SHR; 26-mm TLOC). Cows on the SHR diet had increased DMI and body weight. Although milk yield was unaffected by diet, cows on the SHR diet tended to have increased yields of 4% FCM, ECM, and milk fat. The yields of milk protein and lactose were not affected by diet. Similarly, the proportion of milk components remained unaffected. The feed efficiency (milk/DMI) was higher in cows fed the CON diet, whereas it remained unaffected when expressed as ECM/DMI. Neither rumination nor rumen fermentation parameters were affected by the diet. Overall, the positive effects of corn shredlage on milk performance were relatively small and a result of increased DMI rather than improved rumen fermentation or rumination.HIGHLIGHTS Corn shredlage increased DMI Corn shredlage tended to increase yields of 4% FCM, ECM, and milk fat Corn shredlage did not affect rumination and rumen fermentation